Pelanggaran Pemancingan Ilegal oleh Pelaut Tradisional Pantai Labu di Perairan Malaysia: Perspektif Masalah dan Penegakan Hukum - Putri, Shellya Eka; Sinaga, Sondang Ruth Lovenia; Parangin-Angin, Reh Bungana Beru (Journal of Law & Policy Review, 2024)
Writing this article aims to find out how law enforcement is viewed from the perspective of problems and also the handling of Illegal Fishing carried out by traditional sailors from Pantai Labu in Malaysian waters. The problem is focused on law enforcement in Malaysian waters against Illegal Fishing by traditional seafarers. In order to approach this problem, a theoretical reference is used from the 1982 UNCLOS ratification concerning sea waters or ZEE. The data were collected through interviews and searches through literature studies, as well as utilizing the media and articles related to the issues being discussed and analyzed qualitatively. This study concludes that traditional seafarers from Pantai Labu have been carrying out Illegal Fishing by stealing fish in the Malaysian border waters. Illegal Fishing is subject to sanctions in accordance with the provisions of Article 73 UNCLOS 1982 which relates to Illegal Fishing, if foreign vessels do not comply with the laws and regulations of the coastal state in terms of conservation of fishery resources, the coastal state may arrest the vessel with imprisonment according to age. minimum confinement of 10 days – 2 years and confiscation of vessels and fish caught.